Re-imagining leisure education with Canadian hope: will the caravan of American individualism keep rolling?. Issue 3 (2nd July 2020) - Dieser, Rodney B.
ABSTRACT: Leisure education needs to move beyond an American individualistic model focused on changing or fixing individuals and can be used to change ecological factors and be used in a system-directed and social policy perspective, such as addressing social problems facing Canadian families and communities. Individualistic development models of leisure education are often associated with a person-centred approach – which is when an individual person is placed at the centre of a program or intervention and human services workers look to the person to identify and express leisure needs, interests, goals and strategies to meet goals. In contrast, an ecological approach to change, also known as system-directed change, occurs when strategies are put forth in order to improve communities or other environmental factors in providing human services. Leisure education approaches, linked to Canadian society, are outlined in order to showcase system-directed and social policy-based leisure education.